Survival Value and a Robust, Practical, Joyless Individualism: Thomas Nixon Carver, Social Justice, and Eugenics - Luca Fiorito; Cosma Orsi (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2016)
The aim of this paper is to provide a compressive assessment of Thomas Nixon Carver's thought - from his early formative years in the 1880s to his post WWII career as a journalist and pamphleteer. The main (albeit not exclusive) focus of this paper will be on the theoretical and philosophical coordinates of Carver's "new liberalism" - his own definition - and how this broad vision was intrinsically connected with an explicit hierarchical and eugenic approach to human nature. Just as important, what follows is also an attempt to increase our general understanding of the extent in which eugenic considerations permeated the realm of political economy during the first decades of the last century and how, in some specific cases as that of Carver, this influence persisted after the end of the Progressive Era.
Keywords: B31; B13; B25; 330; T N Carver; Progressive Era; Eugenics